Strategi Guru Dalam Mengembangkan Pembelajaran Mengenal Angka Pada Anak Usia Dini di Ra Ananda Pertiwi - Luthffiah, Alya; Raniyah, Qaulan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to describe teacher strategies in developing number recognition learning for early childhood at RA Ananda Pertiwi. Number recognition is a crucial aspect of early childhood education because it is related to cognitive development, numeracy skills, and children's readiness to enter the next level of education. The research method used was a literature review, compiling various references from relevant books, journals, and articles. The results showed that teachers employed several strategies, including game-based learning, the use of concrete media, the use of visual media, and the integration of numbers into daily activities. These strategies were able to improve children's understanding of numbers, both in recognizing symbols and their future with the number of real objects. The success of the learning was supported by teacher creativity, a pleasant learning environment, and parental support. However, there were still obstacles such as limited facilities, differences in children's abilities, and short attention spans. Overall, the teacher strategies at RA Ananda Pertiwi proved effective in helping children recognize numbers through a creative, innovative approach that aligned with the developmental characteristics of early childhood.